Persepsi Penggunaan Media Pembelajaran Digital dalam Meningkatkan Minat Belajar - Alfianti, Serlina Nur; Rahmah, Eka Naelia (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2024)
The background of the research is based on the rapid development of technological times, now digital technology has entered various aspects of life, including the world of education. Now digital learning media is one of the new innovations applied by MTs Pembangunan Jakarta in increasing student interest in learning. The purpose of this study was to determine the perception of the use of digital learning media in increasing student interest in learning at MTs Pembangunan Jakarta. The research method used is a qualitative research method with a descriptive approach. The research subjects consisted of the Principal, Deputy Principal of the Curriculum Section, Akidah Akhlak Teacher, 4 students of class VII MTs Pembangunan Jakarta. Data collection techniques through field observations, interviews, and documentation. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results showed that the perception of the use of digital learning media at MTs Pembangunan Jakarta can increase students' interest in learning, this can be achieved through the relevance of the use of digital learning media running with the presence of competent teachers in teaching, by operating digital learning provides convenience and also the availability of complete infrastructure facilities, in addition to providing advantages and benefits, of course there are also disadvantages such as signal networks, and teachers who are stuttering in technology. Apart from the shortcomings in the use of digital media, digital learning can make students feel happy because teachers can design attractive teaching materials such as with E-Modules in the SmartMP application, learning with tablets and televisions makes students more focused and attentive to the teacher, involving students in learning such as making groups, discussions, making students more active in learning.